Characteristics of local inflammation of the fibula bone material from Tell Masaikh (Syria) - Mańkowska-Pliszka, Hanna; Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2020)
Inflammatory states usually precede the development of an organ or systemic pathologies. Whether a given infection that causes such a state has a chance to develop, depends on many individual and environmental factors. Post-inflammatory changes can be traced in the osseous material. Therefore, macroscopic, radiological and histological analysis was performed on the upper epiphysis of the right fibula (caput fibulae) with a lesion within the articular surface turned towards the tibia (facies articularis capitis fibulae). The research material came from the excavations led in Tell Masaikh (Syria).